ANTIBACTERIAL ACTIVITY OF FLOWER EXTRACTS FROMHELENIUM MEXICANUM H.B.K. - Barrera-Figueroa , B. E.; Loeza-Lara, P. D.; Hernández-García , A.; Molina-Torres, J.; Molina-Torres , J.; Río-Torres, R. E. N. del; Salgado-Garciglia?, R. (Emirates Journal of Food and Agriculture, 2011)
Helenium mexicanum (Asteraceae) is used in traditional Mexican medicine. Several studies have shown its insecticidal activity but its antibacterial properties have not been studied. The aim of this work was to assess the antibacterial activity of flowers extracts from H. mexicanum on ten human pathogen bacteria by disc-diffusion, broth dilution and bioautographic methods. Eight different extracts were obtained from H. mexicanum flowers and the antibacterial activity was evaluated. The acetone macerates (MA) and the soxhlet-chloroform (SC) extracts showed the highest activity against seven bacterial isolates. The MA extract was fractionated and the highest activity against S. aureus was shown by chloroform (CF) and methanol (MF) fractions, with MICs values of 0.125 mg/mL. Bioautography analysis of CF revealed at least six antibacterial components with different inhibition zones, whereas MF revealed only one inhibitory spot. Given the solubility properties of the active fractions, sesquiterpene lactones may comprise most of the antibacterial active compounds of H. mexicanum. This work systematically demonstrated the antibacterial activity of flower extracts from H. mexicanum.